Testing hypotheses about the harm that capitalism causes to the mind and brain: a theoretical framework for neuroscience research - Kokorikou, Danae S.; Sarigiannidis, Ioannis; Fiore, Vincenzo G.; Parkin, Beth; Hopkins, Alexandra; El-Deredy, Wael; Dilley, Laura; Moutoussis, Michael (Frontiers in Sociology, 2023)
In this paper, we will attempt to outline the key ideas of a theoretical framework for neuroscience research that reflects critically on the neoliberal capitalist context. We argue that neuroscience can and should illuminate the effects of neoliberal capitalism on the brains and minds of the population living under such socioeconomic systems. Firstly, we review the available empirical research indicating that the socio-economic environment is harmful to minds and brains. We then describe the effects of the capitalist context on neuroscience itself by presenting how it has been influenced historically. In order to set out a theoretical framework that can generate neuroscientific hypotheses with regards to the effects of the capitalist context on brains and minds, we suggest a categorization of the effects, namely deprivation, isolation and intersectional effects. We also argue in favor of a neurodiversity perspective (as opposed to the dominant model of conceptualizing neural (mal-)functioning) and for a perspective that takes into account brain plasticity and potential for change and adaptation. Lastly, we discuss the specific needs for future research as well as a frame for post-capitalist research.